MESSAGES AND PERSUASION IN VERBAL AND VISUAL SIGNS OF WORLD VISIONâS ZAMBIA PROJECT CAMPAIGN VIDEO - Arya Putry, Made Yuana (Lingual: Journal of Language and Culture, 2015)
This article aims at describing the analysis result of messages and persuasion modes implied in the verbal and visual signs. The data was taken from a campaign video: World Vision Water - Meet Violet and the Other Children of the Zambia Project - World Vision